An Analysis of Factors Influencing Student’s Problem in Pronouncing Long and Short Vowels - Sulaiman; Muhammad Iqbal Ripo Putra (Penerbit STKIP PGRI Bangkalan, 2017)
The purpose of this research was to find out the students’ ability in pronouncing long and short English vowels and to find out what is the factor causing the problems in pronouncing short and long English vowels. This research was done through descriptive research, the sample was chosen by purposive sampling. There were 6 classes as population and chosen 5 students in each class as a sample to represent all students in every class.The tool of data collecting of this research was minimal pair test as a measurement test and interview. Based on the research finding, it was found that only 2 students that got score with the category “good” (60) and “excellent” (80) from the total of 30 students with the mean score 40,89 that categorized into